Comparative evaluation of hesperetin loaded nanoparticles for anticancer activity against C6 glioma cancer cells - Ersoz, Melike; Erdemir, Aysegul; Duranoglu, Dilek; Uzunoglu, Deniz; Arasoglu, Tulin; Derman, Serap; Mansuroglu, Banu (TAYLOR & FRANCIS LTD, 2019)
The aim of this study was to evaluate anti-cancer properties of hesperetin (Hsp) and hesperetin-loaded poly(lactic-co-glycolic acid) nanoparticles (HspNPs) for glioblastoma treatment. Nanoparticles prepared by single emulsion method had a size of less than 300nm with 70.7 +/- 3.9% reaction yield and 26.4 +/- 1.1% Hsp loading capacity. Treatment of C6 glioma cells with HspNPs for 24 and 48 h resulted in dose- and time-dependent decrease in cell viability, with approximate IC50 of 28 and 21 mu g/mL, respectively (p = .036 for 24 h, p = .025 for 48 h). The percentage of PCNA positive cells decreased to 20% and 10%, respectively, for Hsp- and HspNP-treated cells at concentration of 100 mu g/mL. Treatment with increasing concentrations of HspNPs (25, 50, 75 and 100 mu g/mL) resulted in 9.1-, 7-, 12.5- and 12.7-fold in increase in apoptotic cell number. Optimum doses of Hsp and HspNPs were found to increase oxidative damage in C6 glioma cells. MDA levels, an indicator of lipid peroxidation, were found to be significantly elevated at 75 and 100 mu g/mL exposure concentration of HspNPs with (p = .002) and (p = .018), respectively for 48-h treatment. The results obtained with this study showed biocompatible polymeric nanoparticle systems has great advantages to enhance anti-cancer activity and poor solubility of therapeutic agents. Overall our findings suggest that Hsp-loaded PLGA nanoparticle systems showed significant anti-cancer activity and HspNPs could be used as promising novel anti-cancer agent.
Keywords: Hesperetin; PLGA; nanoparticle; anti-cancer activity; glioblastoma; OXIDATIVE STRESS; LUNG CARCINOGENESIS; FLAVONOIDS; PROLIFERATION; ANTIOXIDANT; SOLUBILITY; HESPERIDIN; APOPTOSIS; TOXICITY; Biotechnology & Applied Microbiology; Engineering; Materials Science